(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2022)
Maintenance of arch length and width are very important in growing patients. Missing teeth may lead to loss of alveolar ridge and may interfare an innovative appliance known as PMS appliance was fabricated insitu. Functions, esthetics and cost effectiveness are the successful outcome of this appliance with minimal components used. A 13 years old girl reported to the department with missing anterior teeth was treated with the same. Appliance fabrication, advantages, limitations and various factors consideration are discussed.